Crossing the Barriers : The Autobiography of Allan H. Spear - Spear, Allan H. (Book collections on Project MUSE., 2010)
Allan Spear had a long and distinguished career as a historian and as a Minnesota state senator. Perhaps best known for coming out as openly gay during his first term in the Minnesota Senate-becoming one of the first elected officials in the nation to do so-Spear was also a leader of Eugene McCarthy's run for the presidency, an organizer against the war in Vietnam, and a key proponent for the establishment of the African-American studies department at the University of Minnesota.